Natural Disaster Damages and Their Link to Coping Strategy Choices: Field Survey Findings from Post‐Earthquake Nepal - Rayamajhee, Veeshan; Bohara, Alok K. (Journal of international development, 2019)
The 7.8 magnitude earthquake that struck Nepal on 25 April 2015, was the worst natural disaster to hit Nepal since 1900. This article reports field survey findings on earthquake damages and ex‐post coping responses adopted by rural households in Sindhupalchowk, Nepal. Subsequently, we conduct empirical analyses to illustrate how earthquake damages influence ex‐post coping strategy choices and potentially limit paths to post‐disaster recovery. The goal of this empirical demonstration is to underscore the need to cater post‐disaster policies in developing countries in ways that expand households' post‐disaster coping strategy choices through market and non‐market mechanisms. © 2018 John Wiley & Sons, Ltd.